2021
DOI: 10.3390/w13182601
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Soil Drying Out and Rewetting on Nitrogen and Carbon Leaching—Results of a Long-Term Lysimeter Experiment

Abstract: As a result of global climate change, heavy rainfall events and dry periods are increasingly occurring in Germany, with consequences for the water and solute balance of soils to be expected. The effects of climate change on nitrogen and carbon leaching were investigated using 21 non-weighable manually filled lysimeters of the UFZ lysimeter facility Falkenberg, which have been managed since 1991 according to the principles of the best management practices and organic farming. Based on a 29-year dataset (precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…However, the moderate drought in late 2009 and 2010, followed by an exceptionally wet year in 2013-2014 across New England may have contributed (U.S. Drought Monitor, 2023; Supplementary Figure 6). Periods of drought reduce soil microbial activity and plant uptake (Rupp et al, 2021) and lead to accumulation of N that is available for flushing thereafter (McClain et al, 2003;Rupp et al, 2021). Indeed, a recent study found that dry periods followed by heavy rainfall can disrupt the water-solute balance in soils, and lead to exceptionally high N export in streams (Loecke et al, 2017;Rupp et al, 2021).…”
Section: Patterns In Stream Water: Do C and N Respond Di Erently To O...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the moderate drought in late 2009 and 2010, followed by an exceptionally wet year in 2013-2014 across New England may have contributed (U.S. Drought Monitor, 2023; Supplementary Figure 6). Periods of drought reduce soil microbial activity and plant uptake (Rupp et al, 2021) and lead to accumulation of N that is available for flushing thereafter (McClain et al, 2003;Rupp et al, 2021). Indeed, a recent study found that dry periods followed by heavy rainfall can disrupt the water-solute balance in soils, and lead to exceptionally high N export in streams (Loecke et al, 2017;Rupp et al, 2021).…”
Section: Patterns In Stream Water: Do C and N Respond Di Erently To O...mentioning
confidence: 99%
“…Periods of drought reduce soil microbial activity and plant uptake (Rupp et al, 2021) and lead to accumulation of N that is available for flushing thereafter (McClain et al, 2003;Rupp et al, 2021). Indeed, a recent study found that dry periods followed by heavy rainfall can disrupt the water-solute balance in soils, and lead to exceptionally high N export in streams (Loecke et al, 2017;Rupp et al, 2021). The decoupling of C and N dynamics is interesting and points to complex dynamics that require further investigation at a regional scale.…”
Section: Patterns In Stream Water: Do C and N Respond Di Erently To O...mentioning
confidence: 99%
“…Constituting the relationships between leaching of NO 3 – and application rates of N fertilizers either by synthetic or organic sources could provide sufficient information to estimate N leaching in similar soil-climatic conditions ( Dybowski et al, 2020 ). Measurements covering several sites in different soil and climatic conditions to establish an empirical model denoting different drought, normal, and saturated years could serve beneficially in the estimation of NO 3 – leaching for certain soil-climatic conditions because of the similarity of other variables which impact the leaching pathways ( Woli and Hoogenboom, 2018 ; Rupp et al, 2021 ).…”
Section: Toward Eco-efficient N Managementmentioning
confidence: 99%
“…Dry conditions reduce not only plant growth and yield but also water percolation below the rooting zone and nutrient leaching and losses by surface runoff, possibly enhancing nutrient use efficiencies (Ullah et al., 2019). In contrast, in wetter conditions, nutrient uptake and yields are higher but so is the potential for nutrient leaching, depressing nutrient use efficiencies (Rupp et al., 2021). Irrigation buffers the variability in precipitation and warming, promoting yields (Luan et al., 2021; Tack et al., 2017; Troy et al., 2015; T. Zhang et al., 2015; X. Zhang et al., 2015).…”
Section: Introductionmentioning
confidence: 99%